The profile of the science department head in the Greater Manila Area - Villanueva, Soledad L. (s.n.], 1971)
This paper presented the characteristics of science department heads in the Greater Manila Area. The basic method used in the study is the Normative Survey Approach and involved 29 science department heads. A similar study on the national level would provide an empirical profile of this local edition of the supervisory staff of the school system.